Pola Penerapan Desain Teknologi Tepat Guna Berbasis Mesin CNC dalam Industri Batik Cap sebagai Akselerasi Produksi Batik Cap - Ike Ratnawati; Abdul Rahman Prasetyo; Iriaji; Alby Aruna; Eka Putri Surya; Adinda Marcelliantika (MES Bogor, 2024)
The pattern of applying appropriate technology design based on CNC machines in the stamp batik industry aims to accelerate production. With this technology, the efficiency and quality of batik stamp production are significantly improved, reducing reliance on manual processes that take a lot of time and effort. The methods used include intensive training and mentoring to batik craftsmen in the use of CNC machines to create batik patterns with high precision. The results show a significant increase in the speed and consistency of production, as well as a decrease in the error rate in making batik motifs. In addition, the use of CNC technology has a positive impact on the productivity and income of batik artisans, ultimately improving their well-being. The pattern of applying this technology not only speeds up the production process but also improves the quality of the final product, so that batik stamp can be more competitive in the global market. It is hoped that this technology can be widely adopted in the batik stamp industry to support the development of the creative industry in Indonesia, increase the competitiveness of local products, and contribute more to the national economy. The adoption of this technology shows that innovations in the production process can provide great benefits to traditional industries such as batik stamping, helping to maintain cultural heritage while keeping up with the times.